Responsiveness of the interrenal tissue of Jundia (Rhamdia quelen) to an in vivo ACTH test following acute exposure to sublethal concentrations of agrichemicals - Cericato, Leonardo [UNESP]; Machado Neto, Joaquim Goncalves [UNESP]; Kreutz, Luiz Carlos; Quevedo, Rosmari Mezzalira; Santos da Rosa, Joao Gabriel; Koakoski, Gessi; Centenaro, Lucas; Pottker, Emanuele; Marqueze, Alessandra; Gil Barcellos, Leonardo Jose (Elsevier B.V., 2009)
As in many aquatic environments, pollution is a widespread problem in Southern Brazil. In our previous work, we demonstrated that sublethal contamination with some agrichemicals impairs the capacity of fishes to elevate cortisol levels in response to an additional acute stressor. In earlier experiments, the experimental design did not allow us to conclude where this effect occurs. In the present work, we used the adrenocorticotropic hormone (ACTH) challenge test to help us identify if the impairment occur in the interrenal tissue. For this purpose, five experiments were conducted, each with one specific agrichemical (methyl-parathion, atrazine + simazine, atrazine, tebuconazole, and glyphosate) in sublethal concentrations of 16.6% of the LC(50-96h), as previously determined. Fish were subjected to the ACTH challenge test protocol as follows: group 1, were non-injected and maintained as the specific control group: group 2 received an injection of the vehicle alone (the saline group); and group 3 receive an injection of ACTH. One hour later, blood samples were taken from the caudal plexus, using sterile syringes. In all specific control groups, the injection of ACTH induced a strong rise in plasma cortisol, compared with the fish injected only with the vehicle and the non-injected group. Fish exposed to methyl-parathion and tebuconazole did not elevate cortisol in response to the ACTH injection, with values significantly lower than the control fish. Fish exposed to sublethal concentrations of atrazine + simazine, atrazine, and glyphosate showed a rise in plasma cortisol very similar to the control fish. We conclude that the ACTH challenge test revealed that R. quelen exposed to sublethal concentrations of tebuconazole and methyl-parathion had a reduced ability to elevate plasma cortisol in response to an intraperitoneal (i.p.) injection of exogenous ACTH, indicating that the interrenal tissue is the site of the impairment within the HPI axis. These ACTH challenge tests also revealed that the impairment of the cortisol response verified in fish exposed to atrazine + simazine and glyphosate, as shown in our previous work, seems to be related to steps of cortisol secretion in higher levels within the HPI axis. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Jundia; Rhamdia quelen; ACTH challenge test; Cortisol secretion; Agrichemicals